A study on conversational repair strategies in Chinese EFL classroom - Li, Bing (Animo Repository, 2008)
The present study investigated conversational repair in Chinese EFL context and understands the dynamic process of EFL classroom interaction. Six Chinese EFL teachers and 92 senior college students in six conversation classes in Fujian Province, People’s Republic of China participated in the study. The data were collected, transcribed and analyzed based on the proposals of Kasper (1985) and Mitchell (1988) on repair sequence and repair strategies, respectively. The traditional pattern of IRE (F) was characterized as the structure of a Chinese EFL conversational class. A conversational repair work was embedded in the expanded IRE sequence. Depending on the trouble source, the Chinese EFL teacher and students showed preference towards self-initiation self-repair and other-initiation self-repair respectively. Surprisingly, repetition was the most frequently used repair strategy by the teachers and the students. More communicative activities are recommended in association with conversational repair work.